2019
DOI: 10.1098/rsos.182135
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of silver nanoparticle-decorated cobalt nanocomposites (Co@AgNPs) and their density-dependent antibacterial activity

Abstract: Magnetic cores loaded with metallic nanoparticles can be promising nano-carriers for successful drug delivery at infectious sites. We report fabrication, characteristic analysis and in vitro antibacterial performance of nanocomposites comprising cobalt cores (Co-cores) functionalized with a varied concentration of silver nanoparticles (AgNPs). A two-step polyol process synchronized with the transmetalation reduction method was used. Co-cores were synthesized with cobalt acetate, and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…This electrostatic attractions destroys the selective permeability via the reacting of Ag-NPs with sulfur and phosphorylated proteins located in the bacterial cell wall causing partial dissolution of the cell membrane [ 48 ]. Nanoparticles enter the cell and causes the liberation of Ag + , which causes enhancement of the reactive oxygen species (ROS) that destroys the enzymes involved in cellular respiration and are ultimately responsible for cell death [ 49 ]. In the same context, Al-Dhabi et al [ 50 ] reported the extracellular synthesis of Ag-NPs from Streptomyces parvus with promising antibacterial activity against diverse pathogens involving S. aureus , S. epidermidi , E. faecalis , B. subtilis , P. aeruginosa , and E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…This electrostatic attractions destroys the selective permeability via the reacting of Ag-NPs with sulfur and phosphorylated proteins located in the bacterial cell wall causing partial dissolution of the cell membrane [ 48 ]. Nanoparticles enter the cell and causes the liberation of Ag + , which causes enhancement of the reactive oxygen species (ROS) that destroys the enzymes involved in cellular respiration and are ultimately responsible for cell death [ 49 ]. In the same context, Al-Dhabi et al [ 50 ] reported the extracellular synthesis of Ag-NPs from Streptomyces parvus with promising antibacterial activity against diverse pathogens involving S. aureus , S. epidermidi , E. faecalis , B. subtilis , P. aeruginosa , and E. coli .…”
Section: Resultsmentioning
confidence: 99%
“…The colour of the reaction solution may change from transparent to light yellow to yellowish brown and finally dark brown depending upon the type of the extract used (as shown in figures 3 and 4 ). This time-dependent colour change during the synthesis (10 min for A. indica AgNPs and 20 min for C. colocynthis AgNPs), actually, indicates the different phases of nucleation and growth process occurring in the reactions [ 26 ]. The free silver atoms (Ag 0 ) accumulate due to van der Waals interactions and Brownian motion to form Ag-nuclei (nucleation process).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the crystallite size ( D ) of both type of extract-mediated AgNPs, the width of prominent Bragg's reflection (111) in each case was used in the Debye–Scherer formula [ 26 ]. …”
Section: Resultsmentioning
confidence: 99%
“…11 They include metal nanoparticles like gold, silica, silver and magnetic iron oxide nanoparticles. 5,12,13 But the use of these metal nanoparticles as drug carriers can pose a threat of metal poisoning within the system. Some of the organically derived nanocarriers like polymeric micelles, liposomes, chitosan-based nanocarriers and polymeric nanogels are good for drug delivery.…”
Section: Introductionmentioning
confidence: 99%